Coping Behaviour and Organisational Commitment: A Correlational Study on College Teachers - Sharm, Sapana (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted to explore the coping behaviour of teachers of government degree colleges of Jammu province. The hypothesis was mainly focused on investigating the nature of coping behaviour of college teachers and to find out the relationship of coping behaviour with organisational commitment of college teachers. By using stratified random sampling method, a sample of 250 college teachers was selected for data collection. Findings revealed that college teachers of Jammu region possess deficient coping behaviour; however, it is independent of the effect of gender. Correlation results indicated no relationship existed between the coping behaviour adopted by the college teachers and their organisational commitment.